ChemInform Abstract: Enantiodivergent Synthesis of the Quinolizidine Poison Frog Alkaloid 195C. Issue 17 (28th April 2014) - Wang, Xu; Li, Jie; Saporito, Ralph A.; Toyooka, Naoki
Abstract The first chiral synthesis of compound (I) and its enantiomer is reported.